2012
DOI: 10.1017/s1751731111001753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous v. daytime grazing on feed intake and growth of sheep grazing in a semi-arid grassland steppe

Abstract: In the Inner Mongolian steppe, China, sheep generally graze during daytime and are kept in yards overnight. Hence, nutrients are not returned to the grassland, which might reduce its long-term productivity. Furthermore, the restricted grazing time may limit forage intake and thus the performance of sheep. The aim of this study was therefore to evaluate the impact of continuous 24-h grazing (CG) v. the common daytime grazing (DG) on herbage mass (HM), feed quality, feed organic matter intake (OMI) and live weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
2
2
Order By: Relevance
“…Therefore we propose that when forage quality is generally high across the range, cattle are able to meet their daily nutrient requirements much faster and thus increasing grazing time allowance under such conditions may be less effective in altering their food intake and performance. In addition, our findings differed from the findings of Muller et al (2011), who found no beneficial effect of 24-h grazing on food intake and performance of sheep in a Mongolian grassland system. However, it is important to note that daytime grazing duration was much longer (14-16.5 h) in the study of Muller et al (2011) than in our study (8-9 h).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore we propose that when forage quality is generally high across the range, cattle are able to meet their daily nutrient requirements much faster and thus increasing grazing time allowance under such conditions may be less effective in altering their food intake and performance. In addition, our findings differed from the findings of Muller et al (2011), who found no beneficial effect of 24-h grazing on food intake and performance of sheep in a Mongolian grassland system. However, it is important to note that daytime grazing duration was much longer (14-16.5 h) in the study of Muller et al (2011) than in our study (8-9 h).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, our findings differed from the findings of Muller et al (2011), who found no beneficial effect of 24-h grazing on food intake and performance of sheep in a Mongolian grassland system. However, it is important to note that daytime grazing duration was much longer (14-16.5 h) in the study of Muller et al (2011) than in our study (8-9 h).…”
Section: Discussioncontrasting
confidence: 99%
“…The FNV of the four species decreased with time, while forage maturation accelerated after June, which was also reported in previous studies (Bailey, 2004;Mekuria & Aynekulu, 2013). As species stop growing, maturation and lignification set in, with an increase in cellulose, hemicellulose and lignin and a decrease in cellular substances, such as proteins (Müller et al, 2014). These patterns are associated with a decrease in ME, IVTD and CP and an increase in NDF.…”
Section: Seasonal Patterns Of Forage Nutritional Value Due To Grazingsupporting
confidence: 87%
“…They live and migrate closely with humans, providing a wide variety of raw sources for items such as food, clothing, fuel, transportation, and religious totems and ornaments for the indigenous population (i.e., Tibetan people) (Xian 2005; Chen et al. 2006; Peng 2010; Müller et al. 2012; Liu et al.…”
Section: Introductionmentioning
confidence: 99%